Profiles of childhood trauma: epidemiological survey results of an educated young community cohort - Faiz Bari, Samira; Zehra, Sehrish; Qureshi, Farhan Muhammad; Aziz , Aiman (International Journal Of Community Medicine And Public Health, 2024)
Background: Childhood trauma is a major threat to the welfare and prosperity of any society. Young adult population is vulnerable due to increasing adverse childhood experiences and the likelihood of serious implications in educational performance and mental health. This survey was aimed to observe the proportion of various types of childhood traumas and their association with different socio-demographic characteristics among young university students of Karachi, Pakistan. Methods: This cross-sectional study was conducted among 300 young university students, during August-December 2023. Initially, cluster sampling was done deemed to the epidemiological survey. Afterwards, from the selected clusters, students from different universities were approached using non-probability convenient sampling technique. Self-reported data were collected through a questionnaire comprising of socio-demographic characteristics along with the types of traumas experienced during their childhood. SPSS Version 26.0 was used to analyse data. Results: Of the 300 university students with a mean age of 22.14±2 years, 55.3% were females. Overall, 63.6% of the participants experienced trauma before 18 years age. The most common trauma types reported were physical/verbal abuse (81%), unlawful touch/sexual abuse (45%), parents separated/divorced (31%) abandoned by parents (20%), lived with an alcoholic/drug addict (18%) or with a mentally ill adult (14%). There were no statistically significant findings between childhood trauma experience and socio-demographic traits. Conclusions: Various profiles of childhood trauma were found prevalent in young university level individuals. Current research does suggest a way forward to prevent this public health issue that can have detrimental consequences on an individual’s mental and physical health and stress reactivity.